Mycobacterium tuberculosis Glyceraldehyde-3-Phosphate Dehydrogenase (GAPDH) Functions as a Receptor for Human Lactoferrin - Malhotra, Himanshu; Patidar, Anil; Boradia, Vishant M.; Kumar, Rajender; Nimbalkar, Rakesh D.; Kumar, Ajay; Gani, Zahid; Kaur, Rajbeer; Garg, Prabha; Raje, Manoj; Raje, Chaaya I. (Frontiers in Cellular and Infection Microbiology, 2017)
Iron is crucial for the survival of living cells, particularly the human pathogen Mycobacterium tuberculosis (M.tb) which uses multiple strategies to acquire and store iron. M.tb synthesizes high affinity iron chelators (siderophores), these extract iron from host iron carrier proteins such as transferrin (Tf) and lactoferrin (Lf). Recent studies have revealed that M.tb may also relocate several housekeeping proteins to the cell surface for capture and internalization of host iron carrier protein transferrin. One of the identified receptors is the glycolytic enzyme Glyceraldehyde-3-phosphate dehydrogenase (GAPDH). This conserved multifunctional protein has been identified as a virulence factor in several other bacterial species. Considering the close structural and functional homology between the two major human iron carrier proteins (Tf and Lf) and the fact that Lf is abundantly present in lung fluid (unlike Tf which is present in plasma), we evaluated whether GAPDH also functions as a dual receptor for Lf. The current study demonstrates that human Lf is sequestered at the bacterial surface by GAPDH. The affinity of Lf-GAPDH (31.7 ± 1.68 nM) is higher as compared to Tf-GAPDH (160 ± 24 nM). Two GAPDH mutants were analyzed for their enzymatic activity and interaction with Lf. Lastly, the present computational studies offer the first significant insights for the 3D structure of monomers and assembled tetramer with the associated co-factor NAD+. Sequence analysis and structural modeling identified the surface exposed, evolutionarily conserved and functional residues and predicted the effect of mutagenesis on GAPDH.